2015
DOI: 10.2147/jbm.s72463
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation therapy in transfusion-dependent thalassemia patients: current strategies and future directions

Abstract: Transfusional iron overload is a major target in the care of patients with transfusion-dependent thalassemia (TDT) and other refractory anemias. Iron accumulates in the liver, heart, and endocrine organs leading to a wide array of complications. In this review, we summarize the characteristics of the approved iron chelators, deferoxamine, deferiprone, and deferasirox, and the evidence behind the use of each, as monotherapy or as part of combination therapy. We also review the different guidelines on iron chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 89 publications
1
32
0
Order By: Relevance
“…In large randomized studies on TM, DFX has been shown to have an efficacy similar to DFO with regard to the reduction in liver iron concentration and serum ferritin levels ( 14 , 15 ). Nevertheless, some patients fail to respond adequately to monotherapy with any of these agents ( 16 ). Comparative effectiveness trials may help to determine the ideal strategy for treating various scenarios of organ-specific iron loading.…”
Section: Introductionmentioning
confidence: 99%
“…In large randomized studies on TM, DFX has been shown to have an efficacy similar to DFO with regard to the reduction in liver iron concentration and serum ferritin levels ( 14 , 15 ). Nevertheless, some patients fail to respond adequately to monotherapy with any of these agents ( 16 ). Comparative effectiveness trials may help to determine the ideal strategy for treating various scenarios of organ-specific iron loading.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with transfusional iron overload usually require iron chelation therapy (ICT) to help decrease the iron burden and to prevent and/or delay long-term complications associated with iron deposition in tissues [14]. There are currently three available iron chelators.…”
Section: New Formulation Of Iron Chelatorsmentioning
confidence: 99%
“…The dose ranges from 20 to 50 mg/kg/day. Though it is an effective drug, limited compliance was reported due to the inconvenience of parenteral administration as well as infectious complications [14].…”
Section: Deferoxaminementioning
confidence: 99%
“…Briefly, it has been assessed that DFX at a dose of 20 mg/kg per day can stabilize serum ferritin levels and LIC, while at doses of 30–40 mg/kg per day is able to reduce these parameters and achieve negative iron balance in patients with transfusional iron overload. 36 …”
Section: Chelation In Ntdtmentioning
confidence: 99%